Arthroscopic Treatment of Isolated Hoffa Fractures - Ercin, Ersin; Baca, Emre; Kural, Cemal (The Journal of Knee Surgery, 2017)
The goal of this study was to evaluate the results of a novel method, arthroscopic fixation of isolated Hoffa fractures.This is a prospective, case series and set at Level 1 trauma center. A total of eight patients with isolated Hoffa fractures who were operated by arthroscopic screw fixation method in the anterior posterior direction with 6.5 mm cannulated screws were followed up prospectively. Same surgical method used for all patients. All patients underwent the same rehabilitation program and active range of motion (ROM) exercises were started immediately. The International Knee Society (IKS) knee and functional scores, postoperative knee ROMs, and time of bone union were used as outcome measurements. Postoperative knee ROMs was compared with the contralateral healthy knee. The mean follow-up time was 29 months (26 − 41 months). At the final review, no significant difference (p = 0.159) was found between the ROM of healthy side and operated side of patients (153.1 ± 4.6 and 150 ± 3.8). The mean IKS knee and functional scores at 12 months were 87.2 ± 5.8 and 96.8 ± 3.7, respectively. Union was achieved in all patients at a mean duration of 3.8 months. Fracture side had no influence on the IKS knee scores, functional scores, and ROM (p = 0.846, p = 0.913, and p = 0.374, respectively). Concomitant intra-articular lesions identified in two patients (%25) during arthroscopy were one anterior cruciate ligament rupture and one medial meniscus tear. Patients undergoing arthroscopic Hoffa fracture fixation have excellent outcomes at average 29 months postoperatively with no apparent complications and no significant loss of ROM. Also 25% of patients had intra-articular injuries that were identified with arthroscopic technique that may have been missed with the open technique. The level of evidence was Level 4 (case series).
Keywords: Hoffa fracture; distal femur; arthroscopic fixation; intra-articular fracture